Islam dan Kosmologi Perempuan - Silmi Novita Nurman (Journal of Gender and Social Inclusion in Muslim Societies, 2020)
This study foccuses on the topic of Woman’s cosmology whose main assumption is that man and woman are two interconnected cosmic entities. This paradigm, later on, is not that imperative since more and more people emphasize the relation of the two in its general sense by promoting Western paradigm which is likely to deny the role of woman in her existence as a human being in this nature. In fact, Islam proposes the idea of woman’s cosmology, which perceives the three designation; nature, soul, God, in one way or another, has a kind of relationship and in the wholesale create a chain of symphony of manifestation and balance. For this reason, it is expected that this study offers a new paradigm in understanding the position of woman, especially her relation to other cosmic entities. Islamic cosmology conceives that man and woman has each own lack and good. Nonetheless, the two beings are a unity which means one is supplement to the other that their differences is only a fortune and not a problem. One is the manifestation of God’s attribute Jalal (The Lord Majesty) and the other is of God’s attribute Jamal (OmniBeauty). By realizing an equal gender relation, the cosmic order will authomatically work in balance and stable. For human being, becoming the most important entities, this will enable them to excecute their task as the ‘Chaliph’ (Guardian/Leader) in the World and manifest their position as the most noble being among all beings in the cosmic)